Assessment and treatment of escape from attention in the form of conversation. (6th November 2020) - Cengher, Mirela; Clayborne, Joy C.; O'Connor, Julia T.
Abstract: The purpose of this study was to evaluate treatment procedures for problem behavior maintained by escape from attention in the form of conversation for a child diagnosed with autism spectrum disorder. After conducting a functional analysis that confirmed this function, we implemented a preference assessment to identify some forms of attention that were not aversive. Treatment consisted of four conditions, implemented in a series of reversals. During each condition, the participant chose from some of the following concurrently available options: three forms of attention, escape from conversation, and escape from conversation with a 2‐min delay. We implemented the delay to reduce (devalue) the reinforcing value of escape from conversation. The participant preferred escape from conversation to social interaction when all four consequences were available immediately. When escape from conversation was possible with a delay, the participant's preference changed to social interaction. Implications for clinical practice and future research are discussed.